Aplicación web para el control de stock en la empresa electromecánica Muquinche, año 2022” - Coloma Gaibor, Robinson Alberto (2022)
The document describes the development and implementation of a web application for stock control in the company "Electromecánica Muquinche". Different modules were designed and implemented to meet the specific needs of users. Users will have the ability to manage product inventory as well as have a global view of stock. For the development of the system, the structured analysis and design model was extracted, which allowed a better understanding of the problem, using observation techniques to organize the processes, inputs and outputs of the system. This document includes diagrams, graphics that show the design used in the system and a user manual so that beneficiaries can use the system without complications. The purpose of this document is to explain the execution of the complete process of carrying out the project.